1996
DOI: 10.1007/s002689900051
|View full text |Cite
|
Sign up to set email alerts
|

Modified Sujura Operation: Long‐Term Results

Abstract: From January 1980 to January 1986 a total of 93 patients with portal hypertension (59 males, 34 females; average age 51.5 years) underwent the modified Sujura's operation. All patients presented with esophageal varices during the preoperative endoscopic workup. Child's risk category was A in 6 patients and B in the remaining 87. Our technique consisted of: (1) devascularization of the upper half of the gastric corpus and fundus; (2) devascularization of the last 10 to 12 cm of the thoracic esophagus; (3) pylor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
3
5
0
Order By: Relevance
“…In our studies, all patients underwent splenic transplantation and transabdominal oesophageal transection, and transection of the esophagus and simultaneous stapled anastomosis were performed. Our results of clinical prospective study suggested that the operation can thoroughly stanch bleeding, although the bleeding rate of portal hypertension gastritis is still as high as 9.1%, which is similar with that from another report [12]. Certain characteristics are responsible for the good hemostasis results: firstly, a very extensive devascularization is performed to achieve portoazygos disconnection at the level of the esophagogastric area, where most variceal hemorrhages occur; secondly, esophageal transection interrupts sub-mucosal three layers varice, which normally do not occur in other types of devascularizations; additionally, only the porto-azygos connections through the esophagogastric are interrupted, and portal perfusion can be maintained.…”
Section: Discussionsupporting
confidence: 93%
“…In our studies, all patients underwent splenic transplantation and transabdominal oesophageal transection, and transection of the esophagus and simultaneous stapled anastomosis were performed. Our results of clinical prospective study suggested that the operation can thoroughly stanch bleeding, although the bleeding rate of portal hypertension gastritis is still as high as 9.1%, which is similar with that from another report [12]. Certain characteristics are responsible for the good hemostasis results: firstly, a very extensive devascularization is performed to achieve portoazygos disconnection at the level of the esophagogastric area, where most variceal hemorrhages occur; secondly, esophageal transection interrupts sub-mucosal three layers varice, which normally do not occur in other types of devascularizations; additionally, only the porto-azygos connections through the esophagogastric are interrupted, and portal perfusion can be maintained.…”
Section: Discussionsupporting
confidence: 93%
“…The encephalopathy rate in the combined group in the present study was 6.63%, which was similar to that in the PCDV group, and the rate was comparable to reported rates of 4.1–38.0% in small stoma and selective shunt procedures [11, 25, 36, 37] and rates of 0–7% [32, 38, 39] in devascularization procedures; the rate in our study was superior to that seen with a nonselective portocaval shunt. The results indicated that the combined procedure was not associated with a high risk of encephalopathy.…”
Section: Resultssupporting
confidence: 87%
“…During the Sugiura procedure, a circular stapler anastomosis has to be constructed in terrain that previously has been devascularized, which results frequently in leakage or stricture of the anastomosis. A transsection below the cardia may reduce the risk for stricture of the distal esophagus [1]. Theoretically, an alternative might be the Collis procedure, which reduces inflow from the area of the stomach fundus into the distal esophagus.…”
Section: Discussionmentioning
confidence: 99%